Simulation and Evaluation of Wired and Wireless Networks with NS2, NS3 and OMNET++ - Ahmed, Waleed (My University, 2015)
Communication systems are emerging rapidly with the revolutionary growth in terms of networking protocols, wired and wireless technologies, user applications and other IEEE standards. Numbers of industrial as well as academic organizations around the globe are bringing in light new innovations and ideas in the field of communication systems. These innovations and ideas require intense evaluation at initial phases of development with the use of real systems in place. Usually the real systems are expensive and not affordable for the evaluation. In this case, network simulators provide a complete cost-effective testbed for the simulation and evaluation of the underlined innovations and ideas. In past, numerous studies were conducted for the performance evaluation of network simulators based on CPU and memory utilization. However, performance evaluation based on other metrics such as congestion window, throughput, delay, packet delivery ratio and packet loss ratio was not conducted intensively. In this thesis, network simulators such as NS2, NS3 and OMNET++ will be evaluated and compared for wired and wireless networks based on congestion window, throughput, delay, packet delivery and packet loss ratio. In the theoretical part, information will be provided about the wired and wireless networks and mathematical interpretation of various components used for these networks. Furthermore, technical details about the network simulators will be presented including architectural design, programming languages and platform libraries. Advantages and disadvantages of these network simulators will also be highlighted. In the last part, the details about the experiments and analysis conducted for wired and wireless networks will be provided. At the end, findings will be concluded and future prospects of the study will be advised.
Keywords: communication systems; networking protocols; wired and wireless networks; network simulators; performance evaluation; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|